Board Structure and Monitoring: New Evidence from CEO Turnovers - Guo, Lixiong; Masulis, Ronald W. (Review of Financial Studies, 2015)
We use the 2003 NYSE and NASDAQ listing rules for board and committee independence as a quasinatural experiment to examine the causal relations between board structure and CEO monitoring. Noncompliant firms forced to raise board independence or adopt a fully independent nominating committee significantly increased their forced CEO turnover sensitivity to performance relative to compliant firms. Nominating committee independence is important even when firms had an independent board, and the effect is stronger when the CEO is on the committee. We conclude that greater board independence and full independence of nominating committees lead to more rigorous CEO monitoring and discipline.